Clinical Practice Guidelines for Hypovolemic Shock. - Alba Enseñat Álvarez; Omar Bárbaro Rojas Santana; Alexis Díaz Mesa; Ariamna Fleites Gómez (Medisur)
Clinical Practice Guidelines for Hypovolemic Shock. It has been defined as the persistence of tissue hypoperfusion, usually associated to blood hypotension as the result of body fluids loss. This document includes a description of the concept and different stages of the disease, aetiological classification and comments about the main elements related with diagnosis and treatment, stressing volemic restoration. It includes assessment guidelines focused on the most important aspects to be accomplished.